(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The objective of the research is to study the effect of organizational conflict management strategies (avoidance strategy, confrontation and disclosure strategy, compromise strategy, competition strategy, and cooperation strategy) on the development of social capital at Tishreen University. The researcher distributed (100) questionnaires to the managers and employees at the university under study. The number of recovered and valid questionnaires which were discharged was (92). The researcher analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect of organizational conflict management strategies (avoidance strategy, confrontation and disclosure strategy, compromise strategy, competition strategy, and cooperation strategy) on the development of social capital at Tishreen University. The researcher also made a number of recommendations, including: The necessity of the study university to conduct field studies from time to time to determine the different levels of organizational conflict and know the reasons behind that and determine the methods for dealing with them in a way that guarantees the interests of all parties, and the need to develop special formations for the creators at the university under study, and to prepare specific mechanisms and practices to reward them financially and morally for a purpose Maintaining their stay inside the university.